2019
DOI: 10.1177/1524838019841598
|View full text |Cite|
|
Sign up to set email alerts
|

The “Neglected” Relationship Between Child Maltreatment and Oral Health? An International Scoping Review of Research

Abstract: Globally, the oral health needs of children who have, or are suspected of having, experienced abuse or neglect has become a focus of concern. It is thus valuable and timely to map the contemporary nature of the research landscape in this expanding field. This review reports the findings of a scoping review of the international empirical literature. The aim was to explore the relationship between child maltreatment and oral health and how this complex issue is addressed in contemporary dental, health and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 71 publications
2
41
0
1
Order By: Relevance
“…The prevalence estimates for most of the ACE indicators were significantly higher for the on-reserve population (Table 3, second column) than those living off-reserve (Table 4, second column). Specifically, mothers living on reserve were more likely to: be younger than 30 3 and 4, second column).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence estimates for most of the ACE indicators were significantly higher for the on-reserve population (Table 3, second column) than those living off-reserve (Table 4, second column). Specifically, mothers living on reserve were more likely to: be younger than 30 3 and 4, second column).…”
Section: Resultsmentioning
confidence: 99%
“…The available literature provides evidence that dental neglect, in the form of S-ECC, is a marker of broader neglect in young children, but this same literature acknowledges that the relationship between poor oral health and child maltreatment is conceptually underdeveloped. 30 On the one hand, it is important for professionals working across dentistry, and in medicine, nursing and social work, to make the link between severe ECC and child neglect so as to allow improvements to be made in care pathways for vulnerable children most at risk for ECC. On the other hand, children are rarely referred to child protection services for dental neglect on its own.…”
Section: Discussionmentioning
confidence: 99%
“…• The review (particularly the review of reviews) identified tensions between safeguarding being everyone's business and identified requirements for training which need to be proportionate to need and other competing roles and responsibilities 15,174 .…”
Section: Implications For Service Deliverymentioning
confidence: 99%
“…make it challenging to access training and development to what are, after all, a relatively small and yet critically important part of their identified learning needs. Bradbury-Jones 2019174 similarly identifies how child safeguarding issues may arise in connection with oral health, pointing out that dental practitioners are well-placed to detect some of the more obvious physical signs of physical neglect in children.Professionals who have continuous contact with children, such as people working in schools and community health services, can play a leading role in recognising, responding to, and supporting maltreated children Gilbert 2009 168 . Other professions, such as paramedics, do not require such continuity in their role in meeting the needs of vulnerable children.…”
mentioning
confidence: 99%
“…There is also evidence that children in OOHC use more tertiary and specialist healthcare services compared with children from similar social and economic backgrounds (Jee & Simms, 2006; Knight et al, 2016) suggesting more complex healthcare needs in this population. However, engagement with and access to health care professionals outside of tertiary care settings is a significant problem and consequently, the broad range of health care needs, including oral health, of children in OOHC often go unmet (Ackert et al, 2000; Bradbury‐Jones et al, 2013, 2021; Carlson, 1996; Conlon & Ingram, 2006; Deutsch & Fortin, 2015; Fussell & Evans, 2009; Jackson et al, 2016; Jee & Simms, 2006; Kortenkamp & Ehrle, 2002).…”
Section: Introductionmentioning
confidence: 99%